Audio Visual And Poster As A Media To Improve Mothers’ Knowledge About Stunting During Covid-19 Pandemic - Levio, Siwu; Wahyuni, Langelo; Sasube, Laurensi Meity (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The incidence of stunting is a chronic nutritional problem experienced by more than half of children suffering from stunting in the world originating from Asia (55 percent) while more than one-third (39 percent) live in Africa. Children who suffer from stunting will be more susceptible to disease and as adults are at risk for degenerative diseases. The impact of stunting is not only in terms of health but also affects the level of intelligence of children. Stunting remains a serious National problem in Indonesia, even during the Covid-19 pandemic there was an increase in the stunting rate of 31.8% in 2020, this figure is still far above the World Health Organization (WHO) standard of 20%. Although the stunting prevalence rate in North Sulawesi is still below the national figure (31.8%) which is 25.5%, there are still areas with a fairly high prevalence of stunting, including North Minahasa Regency at 35%, and Kulu Village including those with a high prevalence of stunting. During the Covid-19 pandemic, where we have to implement social distancing, one way to increase public knowledge about stunting is through audio-visual and posters. This study aims to determine the effect of providing education through audio visuals and posters on mothers' knowledge about stunting during the Covid-19 pandemic in Kulu Village, North Minahasa Regency, Province of North Sulawesi, Indonesia. This is a quantitative research with a quasi-experiment two group pretest-posttest design. Group A was given an intervention using audio-visual and posters, while group B as a control was only given poster media. The population in this study were mothers in Kulu Village who had children under 5 years old (balita), with a sample of 40 mothers who were taken by purposive sampling method. The control and intervention groups were 20 mothers each. The results showed that there was a significant increase in knowledge about stunting in the intervention group, namely mothers using audio-visual and posters (100%), compared to the control group who only used posters (60%). Therefore, audio visuals and posters is highly recommended to be used as educational media during the Covid-19 pandemic.